(3MjGI GdMjhGf GdcHQis - (3eMeO Hf ehSi Hf YjSi GdOejQj GdTGaYj , ceGd GdOjf CHh GdHbGA,J (B808 (3g` s
(3ChdgG (B:s
(3jHOC HHGH GdSjf GdegedI (B:" (3SGHQW (B: (3OGHI ef OhGH GdHMQ s
(3BNQgG (B:s
(3hgPG eG GfJgi Edjg GdZQV eeG jMUd ai gPG GdTCf GdEcJGa hcGf GdaQGZ ef eShOJg ai TgQ QLH GdaQO SfI KdGK hSHYjf hSHYeGFI , hef GdeHjVI ai TYHGf SfI NeS hKeGfeGFI s
(3GdfSNI HgG MhGTs
(3GdfUa GdKGfi ef GdfSNI GdSGHbIs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdeYGQa GdYGeIs